Penerimaan Diri Orangtua pada Anak yang Mengalami Retardasi Mental - Agung Septia Hidayatullah; Erny Hidayati (Empathy : Jurnal Fakultas Psikologi, 2021)
Parental Self-Acceptance in Children with Mental RetardatioÂ This study aims to see a picture of self-acceptance parents of mentally retarded children. The subjects in this study were parents with mentally retarded children. This study consisted of three subjects with the sampling technique used as criterion sampling where there were criteria in it, namely the age of children 10-17 years with mentally retarded. The method used in this research is a qualitative method with a phenomenological approach. Collecting data in this study were observations and interviews and This study aims to see a picture of self-acceptance parents of mentally retarded children. The subjects in this study were parents with mentally retarded children. This study consisted of three subjects with the sampling technique used as purposive sampling where there were criteria in it, namely the age of children 10-17 years. The method used in this research is a qualitative method with a phenomenological approach. Collecting data in this study were observations and interviews and the data analysis technique used was thematic analysis. Trust in this study uses triangulation of methods. Method triangulation comes from observational data and subject interviews.. The results showed that the three subjects had attitudes a good self-acceptance of the presence of children can be seen from all aspects, such as no rejection, not being ashamed of the child's condition, accepting and making community participation an important life lesson, and the principle of life to continue raising children until the end of their life. Based on the research results it can be concluded that the third subject accepts himself well. This can be seen from the first subject who often invites his children to the market and around the housing complex, the second subject believes that his child is a provision and responsibility from God to him, and the third subject often invites his child to keep in touch with his family.